Roman Law and National Socialism. Thoughts on the universality of Roman law - Zoltán Végh (Journal on European History of Law, 2011)
The NS doctrine confronts Roman law from two positions: the dominance of the ethnic (völkisch) concept and the implementation of the 'ancient Germanic' principle 'common good comes before self-interest.' Thus, the 'materialistic world order' of Roman law is already rejected in the 1920 party program with reference to the latter. Regarding the former, anything that could transcend the boundaries of ethnic law and the community is rejected. Therefore, ius gentium and ius naturale, along with the principles of universally recognized norms and human transregional fundamental rights derived from them, are decisively rejected. With some mental gymnastics, H.-H. Dietze manages to invent a new 'Ethnic Natural Law.' – Several paragraphs are devoted to the problems that Roman law doctrine encountered during the NS period.